CT-1 (Cardiotrophin-1)-Gal-3 (Galectin-3) Axis in Cardiac Fibrosis and Inflammation: Mechanistic Insights and Clinical Implications. Issue 3 (March 2019) - Martínez-Martínez, Ernesto; Brugnolaro, Cristina; Ibarrola, Jaime; Ravassa, Susana; Buonafine, Mathieu; López, Begoña; Fernández-Celis, Amaya; Querejeta, Ramón; Santamaria, Enrique; Fernández-Irigoyen, Joaquín; Rábago, Gregorio; Moreno, María U; et al.
Abstract : Myocardial fibrosis is a main contributor to the development of heart failure (HF). CT-1 (cardiotrophin-1) and Gal-3 (galectin-3) are increased in HF and associated with myocardial fibrosis. The aim of this study is to analyze whether CT-1 regulates Gal-3. Proteomic analysis revealed that Gal-3 was upregulated by CT-1 in human cardiac fibroblasts in parallel with other profibrotic and proinflammatory markers. CT-1 upregulation of Gal-3 was mediated by ERK (extracellular signal-regulated kinase) 1/2 and Stat-3 (signal transducer and activator of transcription 3) pathways. Male Wistar rats and B6CBAF1 mice treated with CT-1 (20 µg/kg per day) presented higher cardiac Gal-3 levels and myocardial fibrosis. In CT-1–treated rats, direct correlations were found between cardiac CT-1 and Gal-3 levels, as well as between Gal-3 and perivascular fibrosis. Gal-3 genetic disruption in human cardiac fibroblasts and pharmacological Gal-3 inhibition in mice prevented the profibrotic and proinflammatory effects of CT-1. Dahl salt-sensitive hypertensive rats with diastolic dysfunction showed increased cardiac CT-1 and Gal-3 expression together with cardiac fibrosis and inflammation. CT-1 and Gal-3 directly correlated with myocardial fibrosis. In HF patients, myocardial and plasma CT-1 and Gal-3 were increased and directly correlated. In addition, HF patients with high CT-1 and Gal-3 plasma levels presented an increased risk of cardiovascular death. Our data suggest that CT-1 upregulates Gal-3 which, in turn, mediates the proinflammatory and profibrotic myocardial effects of CT-1. The elevation of both molecules in HF patients identifies a subgroup of patients with a higher risk of cardiovascular mortality. The CT-1/Gal-3 axis emerges as a candidate therapeutic target and a potential prognostic biomarker in HF. Abstract : Supplemental Digital Content is available in the text.